2021
DOI: 10.3389/fmed.2021.688091
|View full text |Cite
|
Sign up to set email alerts
|

A Non-invasive Model for Predicting Liver Inflammation in Chronic Hepatitis B Patients With Normal Serum Alanine Aminotransferase Levels

Abstract: Background and Aims: Chronic hepatitis B (CHB) patients with normal alanine aminotransferase (ALT) levels are at risk of disease progression. Currently, liver biopsy is suggested to identify this population. We aimed to establish a non-invasive diagnostic model to identify patients with significant liver inflammation.Method: A total of 504 CHB patients who had undergone liver biopsy with normal ALT levels were randomized into a training set (n = 310) and a validation set (n = 194). Independent variables were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…( 36,40‐42 ) However, other recent studies have found no significant association between age and liver inflammation activity in patients with CHB. ( 31,43‐45 ) Our results show that age was not associated with significant inflammation in either the univariate analysis or in the multivariate analysis. Different races, HBeAg levels, HBsAg levels, HBV DNA loads, as well as the discrepancy of scoring systems of liver inflammation may partially explain the inconsistent results on the association between age and liver inflammation activity among different studies.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…( 36,40‐42 ) However, other recent studies have found no significant association between age and liver inflammation activity in patients with CHB. ( 31,43‐45 ) Our results show that age was not associated with significant inflammation in either the univariate analysis or in the multivariate analysis. Different races, HBeAg levels, HBsAg levels, HBV DNA loads, as well as the discrepancy of scoring systems of liver inflammation may partially explain the inconsistent results on the association between age and liver inflammation activity among different studies.…”
Section: Discussionmentioning
confidence: 61%
“…Of note, the nonsignificant liver fibrosis group had a lower proportion of significant liver inflammation than the significant liver fibrosis group (5.8% vs. 32.8%). ( 31 ) Moreover, Wei et al found that 39.7% patients with significant liver fibrosis had significant liver inflammation, whereas the percentage was only 7.1% in patients without significant liver fibrosis in a cohort of 186 patients with CHB. ( 32 ) However, the levels of HBV DNA and ALT were not limited in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showed that serum ALT levels alone do not fully reflect histological activity of IT phase. In the same vein, previous studies [9][10][11] found that ALT levels did not indicate the actual inflammation in the liver for the following reasons: i) ALT elevation is associated with the location of inflammation 12 , and ii) the changes in ALT levels occur faster than changes in histology. 13 One of the alternative is, as the authors mentioned 1 , different standards for normal alanine aminotransferase (ALT) levels might be applied according to age.…”
Section: Fundmentioning
confidence: 90%